College Alcohol and Drug Abuse Prevention Programs An Update - Eddy, Margot Sanders; ERIC Clearinghouse on Higher Education; George Washington Univ., Washington, DC. School of Education and Human Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Due in part to the 1989 passage of the Drug-Free Schools and Communities Act Amendments, new programs designed to educate college administrators, faculty, and students about alcohol and other drug abuse have taken new directions and dimensions, involving both campuses and local communities in the process. The higher education community has responded with development of the Network of Colleges and Universities Committed to the Elimination of Drug and Alcohol Abuse, a coalition of institutions initiated by the Department of Education's Office of Educational Research and Improvement and coordinated to eradicate campus substance abuse. The ERIC Clearinghouse on Higher Education will process about 600 selected descriptions of campus programs from Network member institutions for inclusion in a file within the ERIC database. The programs show a wide variety in design, focus, and scope, in areas such as mentoring, peer intervention, pledges and contracts, and demonstrations. The program descriptions also show that individual institutions and student organizations themselves are following through with situation-specific remedies that serve not only the campus community but also the larger society. Contains 10 references. (GLR)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062014.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alcohol Abuse; Colleges; Drug Abuse; Drug Education; Health Education; Higher Education; Networks; Prevention; Program Descriptions; Program Development; School Community Relationship; Substance Abuse; Universities; ERIC Digests; ERIC Publications; ERIC Digests in Full Text